Electric Vehicle Adoption for Sustainable Economic Growth in Greater Madura - Saadah, Siti; Ahmadi, Raden Khaeru; Ainorofiqi, Ainorofiqi (Universitas Muhammadiyah Sidoarjo, 2024)
In the context of global sustainability challenges, the transition from fossil fuel dependency to greener alternatives in transportation is vital. The Greater Madura region of Indonesia, with its substantial natural resources and escalating mobility needs, presents a unique opportunity for implementing electric vehicles (EVs) as a sustainable solution. This study explores the barriers to and facilitators of EV adoption in this region through qualitative methods including interviews and expert judgements with stakeholders across government, industry, academia, and the consumer base. The findings reveal that while there is significant potential for EVs to contribute to green economic growth, challenges such as inadequate charging infrastructure and limited public awareness persist. However, strategic investments in infrastructure, comprehensive policy support, and enhanced public engagement are identified as critical drivers for successful EV integration. The study underscores the importance of multi-stakeholder collaboration in achieving sustainable mobility and economic development in Greater Madura.Highlights: The study identifies critical infrastructural and regulatory barriers to electric vehicle adoption in Greater Madura. It highlights the role of multi-sectoral collaboration in fostering a supportive environment for electric vehicles. The research emphasizes the need for increased public awareness and engagement to facilitate the shift to electric vehicles. Keywords: electric vehicles, green economy, sustainable development, infrastructure development, stakeholder collaboration